The internationalization of higher education in Brazil and its linguistic demands: a petition for English (additional languages) learning institutionalization - Ferreira, Marília Mendes (Letras, 2022)
The present essay aims to reflect on the internationalization of Higher Education which is the background of the articles published in this special issue Academic literacy in English: pedagogical practices in times of internationalization. This discussion will explore the linguistic (English) demands imposed by the internationalization of Higher Education and advocate for the institutionalization of English/additional languages learning and teaching support by the universities. The thesis defended in this piece is that without proper provision and learning of these languages for academic purposes by the universities, internationalization initiatives will be ineffective.